Big power rivalry in East Asia : will it disrupt regional cooperation? - Tan, Seng Chye (2011)
Big power rivalry has re-emerged in East Asia. ASEAN’s centrality may be challenged as a result but should not be sidelined by this renewed rivalry. ASEAN has also to ensure that the agenda for East Asian cooperation